Emergency Department Patient Experiences During the COVID-19 Pandemic. (23rd July 2021) - Karalius, Vytas P.; Kaskar, Saabir B.; Levine, Daniel A.; Darling, Tiffani A.; Loftus, Timothy M.; McCarthy, Danielle M.
Emergency department (ED) utilization changed notably during the coronavirus disease 2019 (COVID-19) pandemic in the United States. The purpose of the study was to gain a more thorough understanding of ED patient experience during the early stages of the COVID-19 pandemic. This study used the consensual qualitative approach to analyze open-ended responses from post-ED patient experience surveys from February through July 2020. Comments were included in the analysis if they pertained to care during the pandemic (eg, mentioned "the virus, " "masks, " "PPE"). A total of 242 COVID-specific comments from 192 unique patients were analyzed (median age 49 years; 69% female). Six themes were identified: visually observed changes, experiences of process changes, expressions of understanding or appreciation, sense of security, COVID-19 disease-specific comments, and "classic" satisfaction comments that align with previous literature on patient experience. The COVID-19 pandemic has challenged health care systems across the world in unique and unprecedented ways. This study identified six themes that better elucidate ED patient experience during an unprecedented public health crisis.